Wireless cooperative networks: partnership selection and fairness - Elsheikh, Elsheikh Mohamed Ahmed; Kai-Kit, Wong (2008)
This paper presents analytical results that formalize fair-and-effective partnership selection for a distributed wireless network where user cooperation is employed to enhance the network performance and each individual user has the responsibility of identifying an appropriate partner, or makes a decision if a partnership opportunity is offered by other users. In particular, a 2-user time-division reciprocal cooperation is used so that the transmitters in a network are arranged into pairs of cooperating users with the aid of the channel state information (CSI) at the user nodes.